PELATIHAN MANAJEMEN PEMASARAN MELALUI PHOTOROOM PADA UMKM DI DESA BRAJA HARJOSARI, KEC. BRAJA SELEBAH, LAMPUNG TIMUR - Jatmiko, Edi; Wahid, Moh. Abdur Rahman; Afifah, Pipit (LPPM STAI DARUSSALAM LAMPUNG, 2023)
UMKM or micro, small and medium enterprises are the backbone of the Indonesian economy. It was proven in 1998 and 2008 that UMKM were strong in facing the economic crisis and were able to act as a safety valve for the economy during a crisis. Until now, the progress of UMKM has been paralleled by technological developments. Technology is developing very rapidly and is important for human life today. The aim of this Community Service (PKM) program is to provide knowledge and skills regarding marketing management to UMKM in Braja Harjosari Village. The specific target is to provide knowledge and skills to UMKM players in business development through training in improving marketing management through photoroom and can also increase the skills of training participants in the photoroom application. The method used in this service is a participatory method, where devotees and partners both participate from start to finish. The implementation stages start from photoroom supervision, evaluation stage. As a result of this training, MSME players know more about marketing management so they are better prepared to face increasingly fierce competition and can generate higher income. and through this marketing management training, UMKM understand more about promotional media.